Prosthechea madrensis, a reconsideration of Epidendrum madrense Schltr. (Orchidaceae: Laeliinae) - Karremans, Adam P. (Instituto de Ecología, A.C., 2009)
Epidendrum madrense, traditionally treated under the synonymy of Prosthechea chacaoensis, is recognized as a distinct species and transferred to Prosthechea. The number, length, and shape of the nectar guides on the labellum are useful taxonomic characters to distinguish closely related species in Prosthechea.